Implementation Strategy of a Community-Based Tourism Approach at Siwang Village Tourist Destination, Ambon City, Maluku Province, Indonesia - Meike Elsa Toisuta; Yamres Pakniany; Alce Albartin Sapulette; Asweres A.F. Termas; Elvis Salouw; Heinrich Rakuasa (Asian Journal of Environmental Research, 2026)
The development of tourist destinations with a community-based tourism approach is one form of alternative tourism that has the potential to be carried out. Tourism destination development activities carried out by the community often unknowingly have implemented a community-based tourism approach, as happened in the tourist destination of Siwang Village, Ambon City. Through a qualitative methodology, this study found that the people in Siwang Village have successfully implemented a community-based tourism approach to develop their tourism potential and attractiveness. Siwang Village is one of the mountainous tourist destinations in Ambon City, Maluku Province, which has been successfully managed independently by optimizing its potential and human resources. This research was conducted in 2021 by making the community key informants and policy makers and tourists additional informants.